2000
DOI: 10.1021/ja001034+
|View full text |Cite
|
Sign up to set email alerts
|

Novel Rearrangements of Enynes Catalyzed by PtCl2

Abstract: Pioneering studies of Murai et al. have shown that PtCl 2 is a versatile catalyst for intramolecular skeletal rearrangements of enynes. 1 These substrates convert (i) into 1,3-dienes via a formal enyne metathesis, 1,2 (ii) into 1,4-dienes if the alkene group is part of an allylsilane (stannane) entity, 3 or (iii) into polycyclic arrays if dienynes are used as starting materials. 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
101
5
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 301 publications
(116 citation statements)
references
References 11 publications
4
101
5
6
Order By: Relevance
“…They found that treatment of these substrates with a catalytic amount of PtCl 2 at elevated temperature (60-80 8C in toluene) resulted in the assembly of the corresponding azabicyclo-[4.1.0]heptenes (Scheme 16). [8,9] Mono-, di-, and trisubstituted alkenes efficiently participated in this process.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [410]hepmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that treatment of these substrates with a catalytic amount of PtCl 2 at elevated temperature (60-80 8C in toluene) resulted in the assembly of the corresponding azabicyclo-[4.1.0]heptenes (Scheme 16). [8,9] Mono-, di-, and trisubstituted alkenes efficiently participated in this process.…”
Section: Formation Of Bicycloa C H T U N G T R E N N U N G [410]hepmentioning
confidence: 99%
“…[8,9] The results are summarized in Scheme 7. In addition to the formation of 10-membered dienes 25, 26, 28, 31 and 32, the cycloisomerization was suitable for production of bicyclic products containing 12-membered dienes and 14-membered tetraenes (27 and 29).…”
Section: Scheme 2 a C H T U N G T R E N N U N G (Pphmentioning
confidence: 99%
“…Die Arbeitsgruppe von Yamamoto [126] [122] das ursprüng-liche Katalysatorsystem mit PtCl 2 so zu modifizieren, dass es auch auf stickstoffverbrückte Verbindungen angewendet werden konnte [Gl. (107)].…”
Section: Enin-umlagerungenunclassified
“…[2][3][4][5] Alternatively, attack of nucleophiles R'OH (alcohols or water) at B gives products of alkoxy-or hydroxycyclization F and G.…”
mentioning
confidence: 99%